Cassava sago in Brazil: a parallel between market research and food labeling (Research, Society and Development, 2021)
The presence of cassava and its derivatives in Brazilian food is expressive, except for cassava sago. Given this scenario, there is a lack of studies that reveal the extension of this food in the Brazilian market. The aim of this work was to elucidate this scenario from market research considering the labeling and advertising information, focusing on the online offer of cassava sago in the Brazilian market. The categories “dry sago”, “mixture for preparing sago desserts” and “ready-to-eat sago desserts” were evaluated considering region of sale and price, quality and identity parameters, list of ingredients, liquid content, nutritional table, portion and homemade measures, information on gluten, lactose and food allergens, packaging and sales or official websites. Eighty-one (81) national products were evaluated, consisting of 75.3% (n=61) dry sago, 19.7% (n=16) mixtures for sago desserts and 5.0% (n=4) ready-to-eat sago desserts. Dry sago showed inadequacies in all categories. The mixtures for preparing sago were adequate regarding labeling of portion and household measures, and information on gluten and lactose. Ready-to-eat sago presented systematic errors for being of the same brand. Therefore, it was possible to deepen the panorama of available products and prices, being the first study carried out for the Brazilian market. Even with a relevant amount of available cassava sago, several brands have inadequate labeling, which proves the need for reformulation. Finally, it is understood that virtual communication channels can be more used to attract the attention of consumers to these products, as long as there is appropriate technical language.